MANEJO DA IRRIGAÇÃO E ABUBAÇÃO NITROGENADA NO FEIJOEIRO CULTIVAR BRS FC 402 - MEDEIROS, Rosevaldo Domingos,; LOPES, Adriano da Silva,; Kraeski, Marcos Jefferson,; FRANCO, Jhonatan da Silva,; MACIEL, Gustavo de França, (ANAIS DO ENIC, 2023)
-